Pengaruh Pengangguran Terbuka Terdidik Universitas Terhadap Garis Kemiskinan Di Provinsi Aceh - Wahyuni, Sri (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
This research aims to analyze the effect of open unemployment at female and male universities on the poverty line in Aceh Province using data from the Central Statistics Agency Aceh for the 2012-2020 period. Next, the data was analyzed using the linear regression analysis method multiple and processed using SPSS (Statistical Product and Service Solutions). This study found that male open unemployment had a positive effect on the poverty line although the unemployment rate for male university educated students is lower in comparison Unemployed university educated women in Aceh Province. Meanwhile, the open unemployed are educated Women's universities have no effect on the poverty line in Aceh Province. Policy What the Aceh regional government needs to pay attention to is providing employment opportunities for educated men's universities and universities, especially in Aceh Province, can produce graduates ready to use in the world of work.